The secularization of the original sin and the self-reform of Humanism - Quintana, Oriol; Sáenz Almazán, Berta (Pensamiento. Revista de Investigación e Información Filosófica, 2024)
The humanist project of modernity required that there be no original sin, as Christianity maintained, that prevented us from achieving ever greater quotas of freedom and progress. Thus, the Enlightenment spoke of the social and political conditions that could hinder human progress, but not of limitations inherent in human nature. By original sin we understand, with the theological tradition, that basic defect that prevents us from attaining certain goods. Over the centuries, some unintended consequences of modernity have led certain humanists to attempt a reform of the basic ideas of their own philosophy. Their reflections, focused on vulnerability, secularize —in a functional and indirect sense— the old idea of original sin in order to think about the limits inherent in our condition.
Keywords: humanism; original sin; secularisation; Levinas; Esquirol